Small-Scale Success: How Palm-Based Products are Thriving in Cottage Industries in Thoothukudi district - Venkatesa Palanichamy Narasimma Bharathi; Kalpana Muthuswamy; Balakrishnan Natarajan; Balamurugan Vasudevan; Suresh Appavu; Rajavel Marimuthu; Dhivya Rajaram (The Bioscan, 2023)
Palmyra (Borassus flabellifer), is highly revered in Tamil culture and known as "Karpaka Viruksham". The palmyra tree produces Neera, a perishable product, and contributes to rural community and development. In this study, 25 palm-based industries were surveyed and convenient sampling method was used. The results of the study revealed, majority of respondents were above 50 years old, with 88% of processing units owned by males. The majority of unit owners had over 30 years of experience, with 72% operating as sole proprietorships. The majority preferred complete control over their businesses for effective decision-making. 96% of processing units established their industries on their own land, while only 4% leased land. The labour force was 96% of units with up to five people, compared to only 4% with 5-10 individuals. Palm processing unit owners sell their palm-based products through channel I, with the majority selling to retailers via wholesalers. Palm jaggery is a natural, healthy product made by extracting sap from palm saplings, treating it with lime, filtering and boiling it, and pouring it into coconut shell molds. The palmyra industry faces challenges like adulteration, labour shortages, price variations, and production difficulties. To ensure sustainability, efforts should focus on planting more trees, protecting existing ones, supporting self-help groups, promoting a Farmer Producer Organization (FPO)-based approach, and modern methods for extending product storage life.